2020
DOI: 10.15587/2519-8025.2020.201416
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different photoperiodic conditions on the protein and oil content in soybean seeds (Glycine Max (L.) Merr.)

Abstract: Мета. З'ясувати вплив різної тривалості фотоперіоду на вміст білка і масла у насінні сортів сої, які різняться за реакцією на фотоперіод. Матеріали та методи. У дослідах використані фотоперіодично нейтральні сорти сої Аннушка, Ятрань, Устя і короткоденний сорт Хаджибей. Рослини вирощували у польових умовах у 2016-2018 рр. на експериментальній ділянці кафедри фізіології і біохімії рослин та мікроорганізмів Харківського національного університету імені В.Н. Каразіна на ділянках 1 м 2 у триразовій повторності. Ві… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Greater accumulation and more complete outflow of assimilation products at a favourable day length causes a greater influx of them to growth points, accelerating the sequential formation and growth of vegetative organs and the transition to the formation of generative organs, which is expressed in earlier flowering of plants. In conditions of unfavourable day length, insufficient flow of assimilation products to growth points with a lower intensity of their accumulation and outflow leads to later formation of generative organs (Hider & Zhmurko, 2020). It has also been shown that in the field, the final weight of the seed can reach 68% to 85% of its potential, depending on environmental conditions (Chiluwal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Greater accumulation and more complete outflow of assimilation products at a favourable day length causes a greater influx of them to growth points, accelerating the sequential formation and growth of vegetative organs and the transition to the formation of generative organs, which is expressed in earlier flowering of plants. In conditions of unfavourable day length, insufficient flow of assimilation products to growth points with a lower intensity of their accumulation and outflow leads to later formation of generative organs (Hider & Zhmurko, 2020). It has also been shown that in the field, the final weight of the seed can reach 68% to 85% of its potential, depending on environmental conditions (Chiluwal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%